2020
DOI: 10.1128/aem.01238-20
|View full text |Cite
|
Sign up to set email alerts
|

Rap-Phr Systems from Plasmids pAW63 and pHT8-1 Act Together To Regulate Sporulation in the Bacillus thuringiensis Serovar kurstaki HD73 Strain

Abstract: Bacillus thuringiensis is a Gram-positive spore-forming bacterium pathogenic to various insect species. This property is due to the Cry toxins encoded by plasmid genes and mostly produced during sporulation. B. thuringiensis contains a remarkable amount of extrachromosomal DNA molecules and a great number of plasmid rap-phr genes. Rap-Phr quorum sensing systems regulate different bacterial processes, notably the commitment to sporulation in Bacillus species. Rap proteins are quorum sensors acting as phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…However, when the Rap–Phr encoding subpopulation gets larger and is no longer in minority in the local neighborhood, the Rap-mediated inhibition of cheating/sporulation becomes detrimental and is alleviated by the inhibition of Rap by its cognate Phr communication peptide ( Pollak et al 2016 ; Kalamara et al 2018 ). Here, the detected presence of Rap–Phr systems on 1,531 MGEs suggest that this dynamic regulation of competence/sporulation may sometimes be dependent on a local density of MGEs rather than on a genuine density of bacterial cells, as shown for plasmids in Cardoso et al (2020) and as hinted in prophages by the observed inhibition of Spo0F-P upon heterologous expression of a prophage-encoded Rap receptor ( Even-Tov et al 2016a ; Bernard et al 2020 ).…”
Section: Resultsmentioning
confidence: 71%
“…However, when the Rap–Phr encoding subpopulation gets larger and is no longer in minority in the local neighborhood, the Rap-mediated inhibition of cheating/sporulation becomes detrimental and is alleviated by the inhibition of Rap by its cognate Phr communication peptide ( Pollak et al 2016 ; Kalamara et al 2018 ). Here, the detected presence of Rap–Phr systems on 1,531 MGEs suggest that this dynamic regulation of competence/sporulation may sometimes be dependent on a local density of MGEs rather than on a genuine density of bacterial cells, as shown for plasmids in Cardoso et al (2020) and as hinted in prophages by the observed inhibition of Spo0F-P upon heterologous expression of a prophage-encoded Rap receptor ( Even-Tov et al 2016a ; Bernard et al 2020 ).…”
Section: Resultsmentioning
confidence: 71%
“…Rap-phrsystems regulate essential processes such as sporulation in bacteria of the B. cereus group (Fazion et al 2018; Cardoso et al 2019) and were identi ed in all studied strains, being found in a higher abundance in plasmids of B. thuringiensis than of the other species of the group. Moreover, the accumulation of these systems in B. thuringiensis plasmids may favor a ne regulation of bacterial metabolism to environmental variations (Cardoso et al 2020). These data are in agreement with the already described plasticity of the B. thuringiensis genome (Gillis et al 2018), enabling this bacterium to better adapt to the environment, possibly due to its complex ecological niche (Argôlo-Filho and Loguercio 2014; Mishra et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Omer Bendori et al (2015) showed that this single amino acid substitution is responsible for the observed resistance of RapP to inhibition by PhrP, and that this inhibition could be restored by repairing the N236T mutation. Similarly, the plasmid encoded Rap63‐Phr63 and Rap8‐Phr8 synergistically modulate sporulation and biofilm formation of B. thuringiensis (Cardoso et al, 2020; Fazion et al, 2018).…”
Section: Regulatory Function and Mechanisms Of The Rap‐phr Cassettesmentioning
confidence: 99%